Нереалізовані можливості: спроби українсько-польського порозуміння (осінь 1939 – перша половина 1941 рр.) - Боляновський, А. (Український історичний журнал, 2020)
Мета дослідження – простежити пошук шляхів українсько-польського діалогу на початковому етапі Другої світової війни. Висвітлено основні
дискусії в українському питанні під час формування політичного курсу польського
уряду в екзилі та його структурних підрозділів від початку війни й до середини
1941 р. Виокремлено головних «гравців» цих політичних процесів та їхні дії. Проаналізовано обставини, хід, наслідки і причини неуспіху. Основну увагу зосереджено також на ініціативах уряду Української Народної Республіки в екзилі щодо
досягнення співпраці з еміґраційним польським урядом та його західними союзниками. Методологія ґрунтується на принципах критичного аналізу архівних джерел, методах порівняльного аналізу джерел та історіографії. Наукова новизна. На підставі мало- або й невідомих документів із польських, британських, американських та канадських архівів висвітлюється мотивація українських
і польських політиків у пошуках компромісів задля співпраці в боротьбі проти
СРСР та нацистської Німеччини. Особливу увагу приділено з’ясуванню проблем,
що супроводжували політичний процес досягнення консенсусу між українцями й
поляками. Висновки. Із боку українського та польського еміґраційних урядів було
докладено багато зусиль для досягнення порозуміння зі спірних питань. Незважаючи на це сторони не змогли дійти згоди через різні погляди на територіальні й інші політичні питання. Суттєва увага до налагодження діалогу у планах польського й українського екзильних урядів може бути розцінена як добрий доказ пошуку ними співпраці на початковому етапі Другої світової війни. The purpose of the research is to investigate the search for ways of
Ukrainian-Polish dialogue, taking into account the specific circumstances of the early
stages of World War II. The article covers the main discussions on the Ukrainian
question during the formation of the political course of the Polish Government-in-
Exile and its subdivisions from the beginning of war to the middle of 1941. The main
circumstances, causes, course, consequences and causes of failure of these conversations
are analyzed. The author also focuses on the initiatives of the Government-in-
Exile of the Ukrainian People’s Republic to cooperate with the Polish Government
and its Western allies. The main "players" and their actions in these political processes
have been identified. The main prerequisites, content, development and reasons for
the failure of their discussions are analyzed. The research methodology is based
on the principles of the critical analysis of archival sources as well as on the method
of comparative analysis of the sources and historiography to the historical research.
The scientific novelty. The author highlights the motivation of Ukrainian and Polish
politicians to seek compromise in order to cooperate in the fight against the Soviet
Union and Nazi Germany on the basis of a wide range of small-known or unknown
documents of Polish, American, Ukrainian and Canadian archival documentary.
A special attention is devoted for studying the problems that have been accompanied
process of achievement of political consensus between Ukrainians and Poles.
Conclusions. Many efforts have been made by the Ukrainian and Polish Governments-
in-Exile to reach consensus on many contentious issues. Nevertheless, Polish
and Ukrainian politicians have failed to reach an understanding due to differing
views on territorial and other political questions. However, significant attention to
establishing a dialogue in the plans of the Polish and Ukrainian emigration governments
can be regarded as good evidence of their search for cooperation at the beginning of World War II.